Estrategias motivacionales aplicables a trabajadores subcontratados en empresas constructoras Mipymes (2017)
In the construction sector, the development of most of its processes and activities for the achievement of a building; as pilotage, foundation, pañete and masonry, among others, are subcontracted by execution time. This practice is mostly recognized in Mypimes companies, since these are organizations that work by project. This situation considerably affects the achievement of the deliverables, because employees respond to a third party, has no sense of direct responsibility or institutional belonging, which leads to low performance, delays, control over the use of inputs, materials and resources, It leads to the failure to achieve success in the development of the project.